Effect of asymmetry of AZ31 magnesium alloy as-extruded and as-rolled medium plates on coiling feasibility at the intermediate temperature - Fangkun Ning; Qichi Le; Xiong Zhou; Yanxia Niu; Yonghui Jia (Journal of Materials Research and Technology, 2021)
The effect of asymmetry of magnesium alloy as-extruded and as-rolled medium plates on coiling feasibility at intermediate temperature was investigated by combining experiment and simulation. Through the mechanical properties, microstructure analysis, FE simulation, and determination of coiling parameter, it was found that activation of the secondary deformation mode reduced the stretching R-value of the plate in the rolling direction (RD) or extruding direction (ED), indicating the plate had a better deformation capacity. More secondary twins are produced on the tensile regions of the plates. The strain gradient of the extruded plate was slightly larger than that of the rolled plate through the geometric necessary dislocation (GND). The prismatic and pyramidal <c+a> slip systems were activated in the tensile zones to improve the deformation ability of the plates on coiling and caused the stress triaxiality fluctuation. Finally, the crimp parameter to ensure crimp success was obtained by analyzing the crimp stress according to the critical tensile stress scopes of the two plates.